Pertumbuhan dan Reproduksi Lalat Musca domestica pada Berbagai Media Perkembangbiakan - Endang Puji Astuti; Firda Ynuar Pradani (Loka Litbang Kesehatan Pangandaran, 2010)
Musca domestica was insect that disturbing human and other animal. Intensity M.Domestica with human living includes public healthy. The aim of research is to observe succeed of M.domestica in breeding wether different place. Larva growth in each stadia was different, 2-4 days average. Its contributed by humidity. On dry container, pupae that succes eksklosi only 50%. Presentation of food show differences of larvae development. 3rd stage of larvae that has enough food is 17mm in length and 12mm in length for larvae withless food. Salty water make larvae growing faster than water without salt. Development of Musca domestica in laboratory influenced by high humidity, preset of food and adaptation of Musca domestica its self.